Existence Results for Singular Boundary Value Problem of Nonlinear Fractional Differential Equation - Yujun Cui (Abstract and Applied Analysis)
By applying a fixed point theorem for mappings that are decreasing with respect to a cone, this paper investigates the existence of positive solutions for the nonlinear fractional boundary value problem: 𝐷𝛼0+𝑢(𝑡)+𝑓(𝑡,𝑢(𝑡))=0, 0<𝑡<1, 𝑢(0)=𝑢′(0)=𝑢′(1)=0, where 2<𝛼<3, 𝐷𝛼0+ is the Riemann-Liouville fractional derivative.